AgSCF3-mediated trifluoromethylthiolation of α, α-diaryl allylic alcohols via radical neophyl rearrangement. Issue 3 (5th January 2017) - Liu, Kai; Jin, Qiao; Chen, Shuang; Liu, Pei Nian
Abstract : A novel example of AgSCF3 -mediated oxidative radical trifluoromethylthiolation of α, α-diaryl allylic alcohols is presented, producing various α-aryl-β-trifluoromethylthiolated carbonyl ketones via radical neophyl rearrangement under mild conditions. Abstract : A novel example of AgSCF3 -mediated oxidative radical trifluoromethylthiolation of α, α-diaryl allylic alcohols is presented, producing various α-aryl-β-trifluoromethylthiolated carbonyl ketones via radical neophyl rearrangement under mild conditions. This protocol involves formation of C(Ar)–C(sp 3 ) and C(sp 3 )–S bonds in one step and tolerates a wide range of symmetrical and nonsymmetrical α, α-diaryl allylic alcohols.